2016
DOI: 10.1293/tox.2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

4-Methylthio-3-butenyl isothiocyanate (raphasatin) exerts chemopreventive effects against esophageal carcinogenesis in rats

Abstract: To examine the effects of 4-methylthio-3-butenyl isothiocyanate on esophageal carcinogenesis, male 6-week-old F344 rats were subcutaneously injected with 0.5 mg/kg body weight N-nitrosomethylbenzylamine three times per week for 5 weeks and fed a diet supplemented with 80 ppm 4-methylthio-3-butenyl isothiocyanate, equivalent to 6.05 mg/kg body weight/day for the initiation stage, 4.03 mg/kg body weight/day for the promotion stage, or 4.79 mg/kg body weight/day for all stages. Although the incidence of lesions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…However, it is more important that MTBITC had no toxic effects at lower doses, which may ensure the safety of low‐dose MTBITC applied as a chemopreventive usage, e.g . , 80 ppm in the previous chemopreventive studies (Okamura et al, ; Suzuki et al, ). Based on the previously reported concentrations of MTBITC in heirloom daikon varieties, such as Karami, Momoyama and Sabaga (67, 44 and 36 mg 100 g −1 , respectively) (Nakamura et al, ), the estimated daily dose of MTBITC exerting toxic effects in the present study was equal to approximately 130–250 g kg −1 BW day −1 daikon.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…However, it is more important that MTBITC had no toxic effects at lower doses, which may ensure the safety of low‐dose MTBITC applied as a chemopreventive usage, e.g . , 80 ppm in the previous chemopreventive studies (Okamura et al, ; Suzuki et al, ). Based on the previously reported concentrations of MTBITC in heirloom daikon varieties, such as Karami, Momoyama and Sabaga (67, 44 and 36 mg 100 g −1 , respectively) (Nakamura et al, ), the estimated daily dose of MTBITC exerting toxic effects in the present study was equal to approximately 130–250 g kg −1 BW day −1 daikon.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, PEITC binds to protein targets more strongly than SFN (because the phenethyl group in PEITC is more hydrophobic and the sulfonyl group in SFN is more soluble, allowing PEITC to bind easily to cysteines), whereas SFN induces the greater generation of ROS than PEITC in vitro (Mi and Chung, ). In different in vivo studies, 80 ppm MTBITC was shown to inhibit NMBA‐induced rat esophageal carcinogenesis during both the initiation and promotion phases (Suzuki et al, ), whereas 500 ppm PEITC exerted chemopreventive effects only during the initiation phase, i.e. failed to inhibit carcinogenesis during the promotion phase in the same rat model (Siglin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ITCs generated from glucosinolates are effective inhibitors of carcinogenesis, and many studies have evaluated the effects of ITCs on the prevention of various cancers in animals and the associated mechanisms of action in vitro (Xu et al, 2006;Navarro et al, 2011;IARC, 2004). Our previous studies showed that MTBITC may provide chemoprevention against esophageal carcinogenesis in rats and may activate Nrf2, the transcription factor related to cancer prevention in human esopha-geal cells (Hirata et al, 2018;Suzuki et al, 2016). The inhibitory effect of MTBITC on N-nitrosomethylbenzylamine (NMBA)-induced esophageal carcinogenesis in rats was observed when administered in both the initiation and promotion phases.…”
Section: Introductionmentioning
confidence: 99%